Confusions and dilemma around hepatic dysfunction associated falciparum malaria: A case report and brief review of the literature - Eka Sianti; Jose Meky Mandei (Indonesian Pediatric Society, 2009)
Malaria remains a big burden in East Indonesia. Severe malaria assaults children in endemic area and leads toenormous morbidities and mortalities.According to the World Health Organization's criteria,recognition of one or more of the following clinicalfeatures should raise the suspicion of severe malariai.e, cerebral malaria (unrousable coma), severe anemia(hemoglobin <5 g/dl), renal failure (creatinine serum> 3 mg/dl), pulmonary edema or adult respiratory distresssyndrome (ARDS), hypoglycemia (glucose < 40 mg/dl),circulatory collapse or shock, disseminated intravascularcoagulation (DIC), repeated generalized convulsions,acidosis (pH < 7 .25), macroscopic hemoglobinuria,hyperparasitaemia ( > 5% of the erythrocytes infested byparasites), or jaundice (bilirubin> 3 mg/dl).l-3Jaundice in malaria due to hepatic dysfunction isa classical case, nevertheless, there are some confusionsand dilemmas in managing it.1 We report a case withjaundice due to hepatic dysfunction and hemolysisassociated falciparum malaria that we treated inGeneral Hospital of Fakfak, West Papua, and providea brief literature review on the matter.